DEVELOPMENT OF DIGITAL FLIPBOOK TEACHING MATERIALS BASED ON LOCAL HISTORY OF THE GUNUNG SAHILAN KINGDOM TO INCREASE INTEREST IN LEARNING HISTORY OF CLASS X STUDENTS OF SMAN 2 TAMBANG: PENGEMBANGAN BAHAN AJAR FLIPBOOK DIGITAL BERBASIS SEJARAH LOKAL KERAJAAN GUNUNG SAHILAN UNTUK MENINGKATKAN MINAT BELAJAR SEJARAH SISWA KELAS X SMAN 2 TAMBANG - Eza Nadila; Ahmal; Yuliantoro (SOSIOEDUKASI, 2025)
This research aimed to develop digital flipbook teaching materials based on the local history of the Gunung Sahilan Kingdom to increase students’ interest in learning history. The study was motivated by the lack of engaging teaching media in history classes, especially at SMAN 2 Tambang, where students were observed to be less interested in conventional materials such as textbooks and PowerPoint slides. Utilizing the ADDIE development model, Analysis, Design, Development, Implementation, and Evaluation the research followed a structured and systematic process. In the analysis phase, the needs and challenges in history learning were identified through interviews and classroom observations. The flipbook content was designed according to curriculum standards and incorporated local historical sources, images, and videos. The product was validated by experts and tested in small (10 students) and large groups (30 students). Results showed that the media was highly feasible, with expert validation scores of 96% and 98%, and student response scores of 91% and 94%. Furthermore, students’ interest in learning history significantly increased, from 44% to 88% in the small group and from 47% to 89% in the large group after using the digital flipbook. This study concludes that digital flipbooks based on local history are an effective and innovative teaching medium that supports contextual, engaging, and technology-integrated learning in history education